2017
DOI: 10.1016/j.parkreldis.2017.09.023
|View full text |Cite
|
Sign up to set email alerts
|

The presence of depression and anxiety do not distinguish between functional jerks and cortical myoclonus

Abstract: Depression and anxiety scores are high and do not discriminate between functional jerks and cortical myoclonus. Quality of life was equally impaired in both sub-groups, but pain was significantly worse in patients with functional jerks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 20 publications
0
5
0
1
Order By: Relevance
“…Patients with FMD have been found to report lower rates in questionnaires than when questioned directly, because of stigma of mental illness and/or because of alexithymia [13,28]. We did not confirm small studies in which psychopathology seems less frequent in functional tremor and myoclonus [12,29].…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Patients with FMD have been found to report lower rates in questionnaires than when questioned directly, because of stigma of mental illness and/or because of alexithymia [13,28]. We did not confirm small studies in which psychopathology seems less frequent in functional tremor and myoclonus [12,29].…”
Section: Discussionmentioning
confidence: 77%
“…A review paper comparing non-epileptic attacks and FMD however, concluded that similarities exceed the differences in terms of demographics and associated psychological and physical symptoms [8]. From individual studies focussing on single FMD non-motor symptoms like depression, anxiety, fatigue and pain seem to be comparably high [9][10][11][12][13]. However, a direct comparison between groups has not been performed.…”
Section: Introductionmentioning
confidence: 99%
“…A significant correlation between objective motor symptom severity and psychological symptom severity (anxiety, depression) has previously been reported in patients with functional myoclonus while it was absent in the organic myoclonus control group (Zutt et al, 2017).…”
Section: Relationship Between Motor and Non-motor Symptomsmentioning
confidence: 75%
“…Other nonmotor features, particularly psychiatric disorders and behavioral problems, are also being recognized as part of the phenotype of certain movement disorders (eg, dystonia). In disorders with cortical myoclonus, almost half the patients experience symptoms of depression or anxiety . Underestimation of these nonmotor features is likely, as we have only recently started considering this to be part of the phenotype.…”
Section: Discussionmentioning
confidence: 99%